2019
DOI: 10.1002/ar.24093
|View full text |Cite
|
Sign up to set email alerts
|

Tail Weaponry in Ankylosaurs and Glyptodonts: An Example of a Rare but Strongly Convergent Phenotype

Abstract: The unusual clubbed tails of glyptodonts among mammals and ankylosaurines among dinosaurs most likely functioned as weapons of intraspecific combat or interspecific defense and are characterized by stiffening of the distal tail and, in some taxa, expansion of the distal tail tip. Although similarities in tail weaponry have been noted as a potential example of convergent evolution, this hypothesis has not been tested quantitatively, particularly with metrics that can distinguish convergence from long‐term stasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Tail clubs are extremely rare across the animal tree of life 114 . The evolution of this structure suggests they experienced an adaptive response to selective pressures imposed by predation (predator deterrence and active defence), which prompted the evolution of skeletal precursors necessary to support the evolution of tail clubs 114 , 115 . Thus we may hypothesize that ankylosaurs may have acted as predator deterrence for the whole herbivorous guild.…”
Section: Resultsmentioning
confidence: 99%
“…Tail clubs are extremely rare across the animal tree of life 114 . The evolution of this structure suggests they experienced an adaptive response to selective pressures imposed by predation (predator deterrence and active defence), which prompted the evolution of skeletal precursors necessary to support the evolution of tail clubs 114 , 115 . Thus we may hypothesize that ankylosaurs may have acted as predator deterrence for the whole herbivorous guild.…”
Section: Resultsmentioning
confidence: 99%
“…In tandem, investigating survivorship and selectivity through mass extinctions, such as the end‐Devonian, among and between lineages (Soul & Friedman, 2017 ; Allen et al ., 2019 ) may reveal more detail on the effects of mass extinctions (Sallan & Friedman, 2012 ; Sallan & Galimberti, 2015 ). Deep‐bodied Palaeozoic actinopterygians also represent an obvious test case for exploring these techniques, for example by quantifying convergence and teasing this apart from shared history (Speed & Arbuckle, 2017 ; Arbour & Zanno, 2020 ). Previous work has examined shifts between marine and non‐marine habitats in other fossil groups (and coincident changes in morphology and disparity; Lamsdell, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that superficially convergent phenotypes do arise via diverse evolutionary pathways and/or developmental mechanisms in different clades ( Ng and Smith 2016 ; Morinaga and Bergmann 2017 ; Bergmann and Morinaga 2019 ; Arbour and Zanno 2020 ). The prevalence of incomplete convergence is now widely appreciated in many different systems, although the detailed underpinnings of incompleteness largely remain to be explored (e.g., Losos 2010 , 2011 ; Kaeuffer et al.…”
Section: Discussionmentioning
confidence: 99%